PERAN SERTA MASYARAKAT DALAM MENSOSIALISASIKAN PONDOK PESANTREN DARUT TAFSIR - Kholidatunur Kholidatunur (Universitas Negeri Jakarta, 2013)
This study attempts to examine and analyze in detail the role of the community in disseminating the Darut Tafsir Islamic Boarding School at the city of Bogor, West Java. For more details, this study examines in detail on